Beyond the game exploring the budding field of Philippine esports journalism - Cabrera, Chloe Cruz 1994-; Congjuico, Teresa S.; University of the Philippines Diliman. College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2019)
This study examined the young field of Philippine esports journalism and explored its current role in the Philippines esports industry. "Esport". or competitive video gaming, has experienced rapid growth and expansion in the Philippines within the last decade. Alongside its growth came the emergence of publications dedicated to reporting on esports news in the Philippines. By examining the evolution of this field born of the digital age, this study provided a look into the operation of local esports publications and how they adapt to the changing preferences of their digital audience. These publications are currently owned by large local esports businesses, and the study used the Political Economy theory to examine the effects of their ownership. The study used one major qualitative research strategy: in-depth interviews with seasoned journalists from the most relevant local esports publications of the past decade. By gathering comprehensive accounts of their experiences, this study sought to provide a better understanding of the evolution of the field, the challenges it faces, and its state in the Philippines today. The study found that certain factors, such as the ownership of publications and the local industry's existing structure, currently limit the freedom of local publications to practice journalism.
Vita.
Thesis (A. B. Journalism)--University of the Philippines Diliman
Includes bibliographical references.
Keywords: Electronic games -- Philippines; Video games -- Philippines